Reproductive phenology of three Syagrus species (Arecaceae) in a tropical savanna in Brazil - Arcanjo Bruno, Morgana Maria; Massi, Klecia Gili; Vidal, Mariana Morais; Hay, John du Vall (Elsevier B.V., 2019)
The seasonal timing of reproductive events in plants is explained by exogenous factors (i.e. climate) and endogenous characteristics. Arecaceae family is an important component of the tropical savanna flora, but the reproductive phenology of these plant species is not well understood. We aimed to: (i) test whether flowering and fruiting timing of the palms Syagrus comosa (Mart.) Mart., Syagrus flexuosa (Mart.) Becc. and Syagrus glazioviana (Mart.) Becc. were seasonal and correlated with precipitation; and (ii) investigate if closely related species overlapped in flowering and fruiting. The study was carried out during four years in three tropical woodland savanna sites in Brazil (Cerrado). At each of the three sites, we randomly tagged 20 adult individuals of each species and monthly monitored them for reproductive phenological events. We counted the number of flowers and of fruits and we compared these data with climatic records (precipitation). To test whether the three palm species flowered and fruited uniformly throughout the year, we applied the Rayleigh Z test. We correlated total rainfall of the month with number of flowers or fruits produced using a Spearman correlation test. Flowering and fruiting timing of the species during the years and across sites were mostly aseasonal and were in general not influenced by precipitation. These palm species had synchronous flowering but did not have synchronous fruiting. Because of the year-round fruit production, S. comosa, S. flexuosa and S. glazioviana might be fundamental species to the maintenance of frugivores. The synchronized flowering is an effective means of attracting pollinators and satiating florivores, improving plant reproductive success. The shifted fruiting peaks may emphasize the role of these palms in providing food for frugivores during the year.
Keywords: Flowering; Fruiting; Syagrus comosa (mart.) mart.; Syagrus flexuosa(mart.) Becc.; Syagrus glazioviana (mart.) Becc.; Brazilian savanna